LITERASI PENDIDIKAN RELASI AGAMA, NEGARA, DAN BUDAYA BAGI ORMAS KEPEMUDAAN ISLAM - Suardi M; Andi Armayudi Syam; Andi Ahmad Malikul Afdal; Herman Herman (LPPM Universitas Bina Bangsa, 2023)
Fractures in relations between nations have occurred in many countries, the component of the division is between religious communities caused by extremism, radicalism, to utterances of hatred, but Indonesia is lucky to have survived the split because of the strong commitment to nationalism which is manifested through the presence of the state and the role of civil society such as Nahdlatul Ulama and Muhammadiyah with their moderate character. Therefore, Islamic youth organizations are expected to be the spearhead of religious moderation learning for the community through educational literacy on religious, state and cultural relations, to unify and strengthen understanding and vision of the importance of religious moderation for the integrity of the nation and state of Indonesia. The stages of this service start with planning time, methods and materials, then carry out educational literacy on religious, state and cultural relations, and end with evaluating activities through question and answer. This service activity succeeded in making the participants more understanding and enthusiastic about maximizing the campaign for religious moderation for the people who are their community with a vision that upholds human values ​​regardless of ethnicity, religion, race, class